Technological future of library and information science - Gopal, Krishan (Authorspress, 2001)
Contents of material: Library technical services. Digital society. Strategic planning. Current technologies. Automated acquisition. Serials and cataloguing in infor age. Evaluation. Preservation. Customer care. Copyright issues. Information education.